Application of Carbon Felt as a Flow Distributor for Polymer Electrolyte Membrane Fuel Cells. Issue 2 (1st January 2019) - Lee, Hojin; Kim, Hyecheol; Kim, Hansung
Abstract : In this work, carbon felt is employed as a flow distributor in polymer electrolyte membrane fuel cells and the fuel cell performance of this design is compared to that of a conventional graphite serpentine channel design and copper metal foam. Experimental results show that carbon felts as flow distributors offer advantages over other flow distributors in terms of enhanced rates of mass transfer due to their levels of high porosity and strong convective flow. As a result, fuel cells with carbon felt as flow distributors perform well and especially in high current regions. In addition, the effects of the hydrophilicity of carbon felt on fuel cell performance are evaluated. The hydrophobic surface of raw carbon felt is rendered hydrophilic via ozone treatment. Ozone-treated hydrophilic carbon felt helps remove water from the hydrophobic gas diffusion layer, decreasing mass transfer resistance. However, the formation of oxygen functional groups by ozone treatment increases the levels of ohmic resistance. Thus, it is necessary to develop highly conductive and hydrophilic carbon felt as a flow distributor for high performance of polymer electrolyte membrane fuel cell.